(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
Expropriation in the social interest for the purposes of land reform is an effective tool in the fight for fair land distribution in our country. It is necessary to correctly apply the tools made available by the Original Constituent Legislator to promote land reform, without, however, completely annihilating private property rights. In this context, the judiciary plays an important role, as a true mediator of forces, which is why it must be careful not to be used as a shield for illegal acts, with disastrous social effects. We must always bear in mind that the right to property cannot override other constitutional rights, such as access to land and human dignity.